Whistle-Blowing Systems and Legitimacy Theory: A Study of the Motivation to Implement Whistle-Blowing Systems in German Organizations - Pittroff, Esther (Journal of business ethics, 2014)
Until now, there has been no theoretical foundation that explains why organizations implement whistle-blowing systems. By understanding whistle-blowing systems as an instrument that is desired by society, the legitimacy theory could be transferred to the whistle-blowing concept. A survey of German managers shows that legitimacy theory may be supported. Further insights into legitimacy theory are given by the motivation for the design of the implemented systems. The survey shows that, in particular, the implementation of external whistle-blowing systems is seemingly not driven by desired effectiveness. This supports legitimacy theory, since it reveals that external systems are symbolic rather than substantive systems. However, the results do not hold for internal whistle-blowing systems because the implementation of internal systems is ostensibly driven by power theories. The results are interesting for the planned statutory whistleblower protection as they reveal a partially restrained attitude toward whistle-blowing. Whistle-blowing systems are not effective if management is not convinced of their benefits.